AN INTERCULTURAL STUDY: FORMS AND NEGATIVE CONSEQUENCES OF SABUNESE AND ROTENESE WOMEN GROUP GOSSIPS - Bili, Yunita R. Bani; Otta, Gracia M. N.; Akoli, Marcelinus Y. F. (Academic Journal of Educational Sciences, 2020)
This study examines gossip in two different ethnicities living in the city of Kupang, East Nusa Tenggara province namely Sabu andRote tribes. This study specifically answers two main questions. First, what kind of gossip is usually discussed by women from both ethnicities.Second, which ethnic group produces more negative impacts from this social conversation. In addition to two questions above, several otherelements were also analyzed in this study such as atmosphere, context, participants, age, ethnicity, education, social distance, and language use.The study employed observation and interviews method in collecting the data. The interview was done by applying close ended questionnaire. Atotal of 36 participants were included as samples and subjects in this study. The result of this study indicates that both ethnicities have a commontopic when gossiping. For example, family problems, recipes, parenting, infidelity and others. Although two ethnicities are equally involved andexperiencing the negative effects of this social conversation, women from the Sabu tribe have a higher level of involvement in terms of verbaland physical fights.